(NsEJSMI^ESKIJ MONITORING ZEMNOJ KORY (B/s - (NnIKOLAEW(B, (NaLEKSEJ wASILXEWI^s; (NiN(B-(NT FIZIKI zEMLI IM(B. (No(B.(N`(B. (N{MIDTAs ((NmOSKWA (B:s (NiN(B-(NTA FIZIKI zEMLI an sssr(B,s, 1986)
(NbIBLIOGR(B.: (NS(B. 277-287 (184 (NNAZW(B.)s
(NaWT(B. (NUKAZANY W OGL(B.s
Keywords: (NgEODINAMIKAs; (NzEMLETRQSENIEs; (NpROGNOZs; (NsEJSMI^ESKIE NABL@DENIQs